Performance Assessment : Sebuah Dilema Penilaian Hasil Pembelajaran - Dwi Setyadi (Jurnal Pendidikan, 2009)
This research is attempted to figure out the nature and essence of performance assessment in the point if view of lecturers of higher educational instituion around Madiun Municipality. Theories have launched their judgement that performance assessment is regarded better than a sole pencil-and-paper test, in terms that it records the broader scope of students achievement, not only cognitively but also affectively and psychomotorically. Inspite of the approval from lecturers that performance assessment is theoretically better than pencil-and-paper test, they (lecturers) are reluctant to implement the performance assessment model, for its complicated natures. The research method applied to get data is survey, so as to draw ‘mapping’ of lecturers responds on performance assessment. The result of the analysis shows contradiction between what lecturers say and what they do in relation to the implentation of performance assessment.